Factors of Human Interaction on the Path to Passenger Satisfaction, Perceived Value, and Intention to Recommend in Airlines - IŞIKÇI, SADİYE OYA (Vedat Veli Çay, 2025)
Intense competition, high costs, and elevated customer expectations characterise civil aviation passenger transportation. It is widely accepted that passenger satisfaction is one of the key achievements in gaining a competitive advantage in this industry. While various factors influence passenger satisfaction, the airline industry inherently requires intensive interaction and communication between cabin crew and passengers, as services are delivered on an individual basis. Cabin services, therefore, play a significant role in the emergence of this satisfaction. This study focuses on four dimensions of human interaction points during service delivery in the cabin: individual care, helpfulness, politeness, and promptness. The aim is to determine domestic passengers’ opinions regarding these variables. Additionally, the study aims to statistically determine the impact of each of these variables on passenger satisfaction and the effects of passenger satisfaction on perceived value and intention to recommend. To achieve these objectives, an online survey was conducted using a quantitative research method, and a convenience sampling technique provided access to 405 respondents’ answers. The collected data were coded and analysed using the SPSS software. The empirical findings obtained through statistical analysis emphasise the importance of airline companies focusing on human factors to enhance customer satisfaction. The research statistically confirms the positive effect of human interaction points such as individual attention, helpfulness, courtesy, and promptness by cabin crew members on passenger satisfaction, as well as the audience of passenger satisfaction on perceived value and intention to recommend. Despite the increasing interest in service quality in the airline industry, the effects of various aspects of human interaction on passenger satisfaction, perceived value, and recommendation intention have been limitedly examined. Therefore, this study aims to fill this gap by addressing the interpersonal interaction dynamics between cabin crew and passengers. Based on these findings, the study provides some assessments that can contribute to the literature and the aviation industry.
Keywords: Airline İndustry; Human Factors; Intention To Recommend; Passenger Satisfaction; Perceived Value